2016
DOI: 10.1371/journal.pone.0167512
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation and Bacterial Translocation: A Link between Impaired Immune Recovery and Frequent Visceral Leishmaniasis Relapses in HIV-Infected Patients

Abstract: The maintenance of chronic immune activation due to leishmaniasis or even due to microbial translocation is associated with immunosenescence and may contribute to frequent relapses. Our aim was to investigate whether patients with HIV-associated visceral leishmaniasis (VL/HIV) who experience a single episode of VL have different immunological behaviors in comparison to those who experience frequent relapses. VL/HIV patients were allocated to non-relapsing (NR, n = 6) and relapsing (R, n = 11) groups and were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 42 publications
3
25
2
Order By: Relevance
“…We showed that relapsing-VL/HIV patients maintained low CD4 + T lymphocyte counts, higher percentages of activated CD4 + and CD8 + T cells, sCD14 and anti-Leishmania IgG3, even 12 months after anti-leishmanial treatment, whereas this immune profile was reverted in non-relapsing-VL/HIV patients after anti-Leishmania treatment (13). This indicates intense activation leading to an exhaustion of the immune response to the parasite, which may contribute to the frequent VL relapses or even faster disease progression (2,14).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…We showed that relapsing-VL/HIV patients maintained low CD4 + T lymphocyte counts, higher percentages of activated CD4 + and CD8 + T cells, sCD14 and anti-Leishmania IgG3, even 12 months after anti-leishmanial treatment, whereas this immune profile was reverted in non-relapsing-VL/HIV patients after anti-Leishmania treatment (13). This indicates intense activation leading to an exhaustion of the immune response to the parasite, which may contribute to the frequent VL relapses or even faster disease progression (2,14).…”
Section: Introductionmentioning
confidence: 80%
“…Accordingly, it is conceivable that the compromising degree of one of these compartments may be related to a deficient immune response. These features may contribute to the lack of parasite control which in turn could explain the frequent relapses in VL/HIV (13,14). Thus, the aim of this study was to evaluate if the gain of T cells observed in NR-VL/HIV patients after anti-Leishmania treatment (13) was related to changes in the mobilization profile of the peripheral TCRVβ repertoire, and whether the thymus is involved in the replenishment of newly T cells, especially in non-relapsing VL/HIV co-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, VL was reported as an independent cause of increased non-specific immune activation, T cell senescence and the lack of immune recovery in virologically suppressed coinfected HIV patients ( 56 , 57 ). In line with T cell exhaustion, chronic immune activation was recently associated with recurrent relapse of VL in HIV patients ( 58 ). Recent research in VL–HIV patients also suggested that weak antigen-specific functional responses or proliferation of T cells after in vitro stimulation was an important predictor of relapse ( 59 ).…”
Section: Immunopathogenesis Of Vl–hiv Coinfectionmentioning
confidence: 98%
“… 11 , 12 Also, chronic immunostimulation induced by Leishmania enhances the multiplication of HIV and further progression of HIV infection to AIDS, depressing immunity by exhaustion of immune resources. 11 , 13 , 14 Therefore, Leishmania –HIV coinfection has negative effects, generating poor outcomes and higher risk of relapse in coinfected patients. Even after successful treatment and HAART use, coinfected individuals present increased levels of CD38 + CD8 + T lymphocytes (pointing to increased cellular activation) and proinflammatory cytokines (MIF, MIP1β, TNF, IL6, IL8, and IL17).…”
Section: Immunoresponse In Vl–hiv-infected Patientsmentioning
confidence: 99%
“…In this way, they have chronic immunoactivation induced by persistence of parasites and/or by microbial translocation though the intestinal barrier, demonstrated by the presence of elevated levels of lipopolysaccharide, soluble CD14, and IFBP in serum levels, the immunopathogenic basis of which could be related to mucosal invasion by amastigotes and systemic lymphocyte depletion. 13 , 15 …”
Section: Immunoresponse In Vl–hiv-infected Patientsmentioning
confidence: 99%